Liver Function-Related Indicators and Risk of Gallstone Diseases—A Multicenter Study and a Systematic Review and Meta-Analysis - Shiyi Li; Pei Zhu; Fangyuan Chen; Wenqian Yu; Linjun Xie; Jing Xia; Peng Jiao; Ping Cui; Chi Zhang; Ye Bai; Guoheng Jiang; Hongyu Li; et al. (Gastroenterology Research and Practice)
Results and conclusions: Totally, 369,931 subjects in CMPEC were included in the study. A total of 28 publications were incorporated into the systematic review and meta-analysis. The pooled analysis suggested that aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total protein (TP), and low albumin (ALB) were positively associated with the risk of GSD. Meanwhile, GSD present to have higher AST, ALT, gamma-glutamyl transferase (GGT), total bilirubin (TBil), globulin (G), and ALP levels and relatively lower TP and ALB levels than the healthy participants. These results were consistent when stratified by the study design, geographic background, and study quality. Only the association between ALP and GSD risk was validated in the UKB cohort. This study suggests liver function indicators were associated with GSD risk. The results may provide the basis for exploring the etiology of GSD and may help clinicians identify high-risk subjects.